Greenhouse gas quantification methods developed under CCAFS adopted in USD 250 million climate-smart agriculture project targeting half a million smallholder farmers - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
P9 supported development of a methodology to quantify GHG emissions from smallholder dairy production and piloted a method for quantifying baseline emissions at regional scale. The methodology and survey method were written into the M&E manual of the World Bank funded Kenya Climate Smart Agriculture Project and the manual has been approved. Therefore, CCAFS-supported scientific methods will be used by the Government in reporting on GHG effects of project interventions, national GHG mitigation actions and national GHG inventory.